2006
DOI: 10.2174/157016206777709447
|View full text |Cite
|
Sign up to set email alerts
|

The Blood-Brain Barrier in NeuroAIDS

Abstract: Nearly every aspect of blood-brain barrier (BBB) function is involved in or affected by HIV-1. The disruption of the BBB tends to be minimal and is not likely the mechanism by which infected immune cells and virus enter the brain. Instead, immune cells, virus and viral proteins likely activate brain endothelial cells and enable their own passage across the BBB by way of highly regulated processes such as diapedesis and adsorptive endocytosis. Viral proteins and cytokines can enter the CNS from the blood and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 111 publications
2
72
0
Order By: Relevance
“…37 Previously, HIV-1 has been proposed to disrupt the integrity of brain endothelial cells, which possess tight junction structures as barrier components similar to those of HRPE cells. 17,[38][39][40][41] Other viruses, such as rotavirus and astrovirus, as well as some bacteria, are known to increase intestinal permeability by disrupting tight junctions as part of their pathogenesis. [21][22][23] Here we show that HIV-1 could also induce disruption of tight junction structures in HRPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…37 Previously, HIV-1 has been proposed to disrupt the integrity of brain endothelial cells, which possess tight junction structures as barrier components similar to those of HRPE cells. 17,[38][39][40][41] Other viruses, such as rotavirus and astrovirus, as well as some bacteria, are known to increase intestinal permeability by disrupting tight junctions as part of their pathogenesis. [21][22][23] Here we show that HIV-1 could also induce disruption of tight junction structures in HRPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been recently demonstrated that HIV penetration into the brain does not involve the disruption of the BBB. Instead, immune cells, viruses, and viral proteins probably activate brain endothelial cells and enable their own passage across the BBB by way of highly regulated processes such as diapedesis and adsorptive endocytosis (Banks et al, 2006). Therefore, understanding how the BBB might be affected by various pathogenic or drug factors holds significant promises for the development of novel pharmacological therapies.…”
Section: Introductionmentioning
confidence: 99%
“…An identical behavior with respect to cells of the monocyte lineage has been evoked in the case of human immunodeficiency virus type 1 (HIV-1) to explain the passage of the virus from the blood to receptive, possibly uninfected tissues (28), as best exemplified by viral spread in the central nervous system (1,11,23,24,27). Although a vast literature exists on the ability of HIV-1 to replicate in either macrophages or dendritic cells (8,22,32,38), blood-circulating monocytes are often considered as an example of a cell type restrictive to HIV-1 infection, much like quiescent lymphocytes (6,16,31,33,36,37,41,43).…”
mentioning
confidence: 96%